Hemangioma of the buccal fat pad - Ali Hassani; Sarang Saadat; Roya Moshiri; Solaleh Shahmirzadi (Wolters Kluwer Medknow Publications, 2014)
Hemangiomas are benign vascular neoplasms characterized by an abnormal proliferation of blood vessels. Buccal fat pad (BFP) is a rare place for hemangioma. In this report, clinical, radiographic, and histopathological findings are described in a rare case of hemangioma with phleboliths involving the BFP, and a review is made of the international literature on this subject.